ANALISIS PRAKTIK CICIL EMAS DAN STRATEGI PEMASARANNYA DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH DI BANK SYARIAH INDONESIA - Fajriani, Nur; Lawang, Hasanna; Subaedah; Darmawangsa , Andi; Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the rapid development of Islamic financing products, particularly gold installment financing, which has become an alternative investment for the community. The aim of this research is to analyze the practice of gold installment financing and its marketing strategies at Bank Syariah Indonesia (BSI) KCP Polewali Mandar, as well as to assess their compliance with Islamic economic law principles. This study employs a qualitative method with an empirical juridical approach. Data were collected through observation, semi-structured interviews, and documentation involving bank officers and customers. The data analysis process includes data collection, data reduction, data presentation, and conclusion drawing. The results indicate that the gold installment practice at BSI KCP Polewali Mandar has been implemented systematically through several stages, including application submission, feasibility analysis, gold procurement, execution of murabahah and rahn contracts, installment payments, and final delivery of gold. The marketing strategies applied include direct approaches (canvassing), digital communication, and public education. Overall, both the practice and marketing strategies are in line with Islamic economic law principles, such as justice, honesty, transparency, and the avoidance of riba and gharar. However, challenges remain, particularly the low level of Islamic financial literacy among the public, which leads to misconceptions regarding margin and contract concepts. Therefore, increased education and socialization are necessary to enhance public understanding of gold installment products.